Non-Compliance with The Health Protocol in The Mosque - Febri Tory (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
Uncertainty about when COVID-19 will end, in 2020, in Indonesia, people have experienced social distancing and have experienced the new normal. There has been a lot of non-compliance. For example in mosques, quite a lot of people don't follow health protocols, which we know 3M (wearing masks, washing hands, and maintaining distance) as a symbol of preventing COVID-19. The aims of this study are 1) to describe the general description of non-compliance with health protocols; 2) Examine reasons people do not comply with 3M protocols. This research is qualitative research with a descriptive design. Data was collected employing in-depth interviews. The results showed that the problem was marked by a conflict between worldview and reality in responding to problems starting from the rules for closing mosques in the midst of a pandemic and the emergence of new healthy lifestyle provisions in mosques. In the above conditions, there is a possibility of inability and reluctance to comply with Government recommendations.